Bone Mineral (31)P and Matrix-Bound Water Densities Measured by Solid-State (1)H and (31)P MRI - Seifert, Alan C. (2014)
Bone is a composite material consisting of mineral and hydrated collagen fractions. MRI of bone is challenging due to extremely short transverse relaxation times, but solid-state imaging sequences exist that can acquire the short-lived signal from bone tissue. Previous work to quantify bone density via MRI used powerful experimental scanners. This work seeks to establish the feasibility of MRI-based measurement on clinical scanners of bone mineral and collagen-bound water densities, the latter as a surrogate of matrix density, and to examine the associations of these parameters with porosity and donors’ age. Mineral and matrix-bound water images of reference phantoms and cortical bone from 16 human donors, ages 27-97 years, were acquired by zero-echo-time (31)P and (1)H MRI on whole body 7T and 3T scanners, respectively. Images were corrected for relaxation and RF inhomogeneity to obtain density maps. Cortical porosity was measured by micro-CT, and apparent mineral density by pQCT. MRI-derived densities were compared to x-ray-based measurements by least-squares regression. Mean bone mineral (31)P density was 6.74±1.22 mol/L (corresponding to 1129±204 mg/cc mineral), and mean bound water (1)H density was 31.3±4.2 mol/L (corresponding to 28.3±3.7 %v/v). Both (31)P and bound water (BW) densities were correlated negatively with porosity ((31)P: R(2) = 0.32, p < 0.005; BW: R(2) = 0.63, p < 0.0005) and age ((31)P: R(2) = 0.39, p < 0.05; BW: R(2) = 0.70, p < 0.0001), and positively with pQCT density ((31)P: R(2) = 0.46, p < 0.05; BW: R(2) = 0.50, p < 0.005). In contrast, the bone mineralization ratio (expressed here as the ratio of (31)P density to bound water density), which is proportional to true bone mineralization, was found to be uncorrelated with porosity, age, or pQCT density. This work establishes the feasibility of image-based quantification of bone mineral and bound water densities using clinical hardware.